The S-PLUS Fornax Project (S+FP): SExtractor detection and measurement of nearby galaxies in large photometric surveys - Haack, Rodrigo Facundo (2024)
All-sky multiband photometric surveys represent a unique opportunity of exploring rich nearby galaxy clusters up to several virial radii, reaching the filament regions where pre-processing is expected to occur. These projects aim to tackle a large number of astrophysical topics, encompassing both the Galactic and extragalactic fields. In that sense, generating large catalogues with homogeneous photometry for both resolved and unresolved sources that might be interesting to achieve specific goals, imposes a compromise when choosing the set of parameters to automatically detect and measure such a plethora of objects. In this work, we present the acquired experience on studying the galaxy content of the Fornax cluster using large catalogues obtained by the Southern Photometric Local Universe Survey (S-PLUS). We realized that some Fornax bright galaxies are missed in the S-PLUS iDR4 catalogues. In addition, Fornax star-forming galaxies are included as multiple detections due to overdeblending. To solve those issues, we performed specific SExtractor runs to identify the proper set of parameters to recover as many Fornax galaxies as possible with confident photometry and avoiding duplications. From that process, we obtained new catalogues containing 12-band improved photometry for ∼ 3 × 106 resolved and unresolved sources in an area of ∼ 208 deg2 in the direction of the Fornax cluster. Together with identifying the main difficulties to carry out the study of nearby groups and clusters of galaxies using S-PLUS catalogues, we also share possible solutions to face issues that seem to be common to other ongoing photometric surveys.